2007
DOI: 10.1021/bi0616605
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Conformational Epitope Common to Non-Native and Fibrillar Immunoglobulin Light Chains

Abstract: Amyloid fibrils and partially unfolded intermediates may be distinguished serologically from native amyloidogenic precursor proteins or peptides. In this regard, we had previously reported that the IgG1 mAb 11-1F4, generated by immunizing mice with a thermally denatured variable region fragment of the human Igκ4 Bence Jones protein Len, reacted specifically with light chain (LC) fibrils, irrespective of κ or λ isotype but, notably, did not with native molecules (Hrncic, R. et al. (2000) Am. J. Pathol. 157, 123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 49 publications
3
70
0
Order By: Relevance
“…Immunohistochemical analysis revealed that mAB 11-1F4 recognized light chain fibrils regardless of their V L subgroup. The specificity of this antibody for AL fibrils (I, II, IV, 1, 3, 6, 8) was shown by Europium-Linked Immunosorbant Assay (EuLISA) where an EC 50 value (concentration of antibody at half maximum binding) for binding was ~130 ± 39 nM (O'Nuallain et al, 2007). The interaction of mAB 11-1F4 with native and fibrillar light chain LEN components was also checked by EuLISA and the antibody had similar avidity with both components.…”
Section: Antibodiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Immunohistochemical analysis revealed that mAB 11-1F4 recognized light chain fibrils regardless of their V L subgroup. The specificity of this antibody for AL fibrils (I, II, IV, 1, 3, 6, 8) was shown by Europium-Linked Immunosorbant Assay (EuLISA) where an EC 50 value (concentration of antibody at half maximum binding) for binding was ~130 ± 39 nM (O'Nuallain et al, 2007). The interaction of mAB 11-1F4 with native and fibrillar light chain LEN components was also checked by EuLISA and the antibody had similar avidity with both components.…”
Section: Antibodiesmentioning
confidence: 93%
“…The interaction of mAB 11-1F4 with native and fibrillar light chain LEN components was also checked by EuLISA and the antibody had similar avidity with both components. However, the fibrils had a ~2 fold reduction in signal (O'Nuallain et al, 2007). Peptide mapping was used to determine the cryptic epitope; it is located in the first 18 amino acids of the variable light chain domain and a prolyl residue at position 8 is necessary.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody Binding and Competition Assays-HC and antibody reactivity with amyloid fibrils, CAPS, and elastin fibrils was determined at 37°C using a europium (Eu 3ϩ )-based fluoroimmunoassay (EuLISA) (35) or ELISA. Antibodies or HCs were serially diluted in assay buffer (1% BSA in PBSA) and tested (100 l/well) in activated, high binding microtiter plate wells (COSTAR, Corning, NY) that were coated with 400 ng of target protein and blocked with 1% BSA (Sigma-Aldrich) in PBSA.…”
Section: Methodsmentioning
confidence: 99%
“…The statistical comparisons used paired and unpaired Student's t tests. (25) in our standard EuLISA (35). Following limiting dilution subcloning, two independent hybridomas, F1 and F2, were isolated that bound to LC fibrils with molar antibody concentrations that obtained half-maximum binding (EC 50 ) values of ϳ20 nM ( Fig.…”
Section: Methodsmentioning
confidence: 99%